The Effect of Entrepreneurship Learning and Motivation on Entrepreneurial Interest: The Role of Creativity as an Intervening Variable - Alim Bahri; Gamar Al Haddar; Indah Wati; Un Dini Imran; Salim Diarra (Universitas Negeri Makassar, 2023)
This study aims to determine the direct effect and indirect effect of entrepreneurship learning and motivation on entrepreneurial interest through creativity as a student intervening variable. The research method used in this research is quantitative. The population in this study were all active students of the entrepreneurship study program with a sample of 100 students. directly entrepreneurship learning and motivation have a significant effect on entrepreneurial interest in entrepreneurship study program students. But for the effect of entrepreneurship learning and motivation on creativity there is no significant effect. While indirectly, entrepreneurship learning and motivation affect entrepreneurial interest through creativity. This research can be a reference for teaching staff or lecturers to be able to direct and guide students regarding the development of entrepreneurial interest, students are expected to deepen their interest in business management so that they are not focused on the knowledge produced, but also able to do business and develop it.